Decision support systems K-9 dog selection in PT. Diana Abadi Santosa - Pambudi, M. Indra Nurdin Unggul; Wibowo, Januar; Amelia, Tan (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
PT. Diana Abadi Santosa is a company that one of their business is in motion provide service. PT. Diana Santosa Abadi is constrained in the decision to choose K9 dog that used to resolve something case. In addition the company has not apply a computerized system and is still doing manually. This condition causes the company can not take good decisions in choosing and deciding K9 dog that according to the case or the existing problems. Based on the description above, needed a decision support system in the company. The system consists of the K9 dog needs, and recommend the selection of K9 dog that suits as required. From the test results of decision support systems in PT. Diana Abadi Santosa is concluded that the information system created to help in selection process of K9 dog and recommend the selection of K9 dog as required.